2022
DOI: 10.3390/diseases10020031
|View full text |Cite
|
Sign up to set email alerts
|

Neck Circumference as a Screening Tool for Metabolic Syndrome among Lebanese College Students

Abstract: Metabolic syndrome (MetS) is a cluster of symptoms that, when present, increase the risk for cardiovascular disease. There is a need for reliable screening tools that are ethnically sensitive. Two hundred and sixty-six college students were assessed anthropometrically. They had a fasting blood sample drawn, and blood pressure measured. They then completed a demographic questionnaire and The International Physical Activity Questionnaire (IPAQ). The prevalence of MetS was found to be 10.1% in males and 4.5% in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Firstly, the multifaceted diagnosis of preMetS and MetS, due to the necessity of intricate physical examinations and clinical metrics 55 , is challenging to widely implement in community screenings. Secondly, the use of different instruments for the complex assessment of ve risk factors can lead to signi cant measurement errors and ine ciencies 56,57 , especially in large-scale screening projects. Additionally, we found that WHtR may be a crucial non-invasive screening indicator for preMetS (JCDCG), with its identi cation ability showing no signi cant difference compared to TYG (P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the multifaceted diagnosis of preMetS and MetS, due to the necessity of intricate physical examinations and clinical metrics 55 , is challenging to widely implement in community screenings. Secondly, the use of different instruments for the complex assessment of ve risk factors can lead to signi cant measurement errors and ine ciencies 56,57 , especially in large-scale screening projects. Additionally, we found that WHtR may be a crucial non-invasive screening indicator for preMetS (JCDCG), with its identi cation ability showing no signi cant difference compared to TYG (P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between total cholesterol and NC was observed only in men [ 23 ]. However, a study in Lebanon showed that NC was only associated with LDL-C and triglyceride in males and LDL-C, total cholesterol, and systolic blood pressure in females [ 24 ]. Differences observed in studies results could be due to racial and geographic disparities in populations, the method used to measure NC in particular research, and risk factors that have been adjusted in the analyses [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…NC measurement does not have the limitations of waist circumference measurement; it is convenient, reliable, and does not require undressing. This can be helpful in hijab-wearing communities or people with body image issues [ 24 ]. However, the measurement of NC in individuals with thyroid disease and neck masses is limited [ 27 ].…”
Section: Discussionmentioning
confidence: 99%